CGIAR's Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion initiative - International Livestock Research Institute (2022)
Take a sneak peek at CGIAR’s Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) initiative, which aims to demonstrate that improvements in livestock productivity can offer a triple win: generating improved livelihoods and nutritional outcomes; contributing to women’s empowerment; and, reducing impacts on climate and the environment. The SAPLING initiative is packaging and scaling out tried-and-tested, as well as new, innovations in livestock health, genetics, feed and market systems. The initiative focuses on livestock value chains (beef, dairy, pigs and small ruminants) in seven countries across Africa and Asia – Ethiopia, Kenya, Uganda, Tanzania, Mali, Nepal and Vietnam.